Studies of Fruit Bats on Negros Island, Philippines - Cariño, Apolinario B. (Silliman Journal, 2022)
The current status of population of fruit bats in some forests of Negros Island was assessed between March 1999 and March 2003. Bats were studied using mist nets and direct observations at their roost sites and in captivity at the A.Y. Reyes Zoological and Botanical Garden of Silliman University. A total of twelve species of fruit bats were recorded; namely, Acerodon jubatus, Cynopterus brachyotis, Eonycteris spelaea, Haplonycteris fischeri, Harpyionycteris whiteheadi, Macroglossus minimus, Nyctimene rabori, Ptenochirus jagori, Pteropus hypomelanus, P. pumilus, P. vampyrus, and Rousettus amplexicaudatus. A new island record of the Greater Bamboo Bat Tylonycteris rohustula was first recorded in Canaway, Mantikil, Siaton, Negros Oriental. Species A. jubatus, P. vampyrus, and P. hypomelanus were observed roosting in thousands and in hundreds at Calinawan-Moratorium Area, Apo Island, Sta. Catalina, Vallehermoso, and San Jose in Negros Oriental and in Patag, Mambucal-Murcia, and Danjugan Island, in Negros Occidental. The data gathered have been used to develop a community-based conservation education program aimed at increasing awareness of the importance of bats in the ecosystem. A local community and the Province of Negro3 Oriental have also initiated significant protective measures for the conservation of this species. On Negros Island, fruit bats are heavily hunted especially in their roosting and feeding sites.